Design of a simulation program using digital video processing method to determine the thermal expansion of materials - (:unkn) unknown (My University, 2012)
The present report describes the realization of an educational simulation program to determine the amount of linear thermal expansion in experimental materials. An interferogram signal produced from an interferometric measurement system was modeled as a video signal in a computer environment. A simulation program was designed from the model signal in order to detect the amount of expansion in materials. The simulation program determined the amount of to heat by detecting the number of fringes in interferogram video signals of the material. This simulation program facilitated experimental studies in academic institutions which are deprived of interferometric measurement systems. © Sila Science.
Keywords: Computer science engineering education; Digital video processing; Interferometry; Measurement